In situ minimally invasive 3D printing for bone and cartilage regeneration - a scoping review - Maintz Michaela; Tomooka Yukiko; Eugster Manuela; Gerig Nicolas; Sharma Neha; Thieringer Florian M.; Rauter Georg (Current Directions in Biomedical Engineering)
Advancements in personalized medicine, threedimensional (3D) printing, miniaturization, and robot-assisted surgery are driving innovation in tissue engineering. A novel approach, known as in situ printing, focuses on the direct deposition of materials at the surgical site. Using the in situ printing approach, bone and/or cartilage defects can be addressed with high precision. Furthermore, highly customized 3D printed tissue constructs or implants can be deposited directly inside the body. Currently, most applications of in situ printing are limited to areas near the skin or open surgeries. Even though a minimally invasive approach would bring clinical benefits, only a few research groups have focused on this field. In this scoping review, we provide an overview of the current state of in situ minimally invasive 3D printing technology for bone and cartilage regeneration and discuss its advantages and current challenges.